Avian E2A Expression Level Variation Associated with Phenotypic Variation of Two Chinese Indigenous Duck Breeds, (Anas platyrhynchos) - Mekki, Dafaalla M.; Liang-yong, Bian; Jin-yu, Wang; Yan, Yang; Yabo, Yu; Musa, Hassan H. (International Journal of Poultry Science, 2006)
Semi-quantitative polymerase chain reaction (RT-PCR) was applied to quantify and compare variations in avian E2A expression level between two Chinese indigenous duck breeds for different tissues. Six primer combinations in addition to beta-actin as an internal control were used. The expression level of E2A was significantly (p< 0.05) higher in kidney tissues than lung tissues for both Gao you and Kun shan indigenous duck breeds. The variability of gene expression between two breeds showed 34.35% and 60.70% higher expression in Gao you breed than Kun shan breed for kidney and lung tissues, respectively. Differences were found to be significant (p< 0.05) only for expression level in lung tissues. No significant effect of sex upon E2A expression was detected. The association between E2A relative expression level and body weight was found to be positive and moderate for the genetically lean breed (Gao you), while it was negative and has low values for genetically heavy breed (Kun shan).